Penetapan Awal Bulan Kamariah dan Permasalahannya di Indonesia - Dedi Jamaludin (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2018)
Determination of the beginning of the lunar month in Islam begins with the appearance of the new moon, which is an issue of ijtihad. Based on research shows that in rukyat there are many weaknesses so that this method needs to be elaborated with modern technology (in this case reckoning). Research and calculations carried out by experts on reckoning show that the data generated has always provided very accurate results without leaving significant differences. Basically, Reckoning is a scientific building, so it is strongly influenced by each epistemic discourse. Wujudul hilal carried by Muhammadiyah and imkanur rukyat by the Government has its own characteristics. So, the limit of equilibrium (read: balance) reckoning and imkanur rukyat lies in the extent to which the two communicate with each other, rather than taking distance.Keywords: Early Month, Reckoning, Rukyat, Matlak